Ex-situ Bioremediation of U(VI) from Contaminated Mine Water Using Acidithiobacillus ferrooxidans Strains - Romero-González, Maria; Nwaobi, Bennett C.; Hufton, Joseph M.; Gilmour, Daniel J. (Frontiers in Environmental Science, 2016)
The ex-situ bioremoval of U(VI) from contaminated water using Acidithiobacillus ferrooxidans strain 8455 and 13538 was studied under a range of pH and uranium concentrations. The effect of pH on the growth of bacteria was evaluated across the range 1.5 – 4.5 pH units. The respiration rate of At. ferrooxidans at different U(VI) concentrations was quantified as a measure of the rate of metabolic activity over time using an oxygen electrode. The biosorption process was quantified using a uranyl nitrate solution, U-spiked growth media and U-contaminated mine water. The results showed that both strains of At. ferrooxidans are able to remove U(VI) from solution at pH 2.5 – 4.5, exhibiting a buffering capacity at pH 3.5. The respiration rate of the micro-organism was affected at U(VI) concentration of 30 mg L-1. The kinetics of the sorption fitted a pseudo-first order equation, and depended on the concentration of U(VI). The KD obtained from the biosorption experiments indicated that strain 8455 is more efficient for the removal of U(VI). A bioreactor designed to treat a solution of 100 mg U(VI) L-1 removed at least 50% of the U(VI) in water. The study demonstrated that At. ferrooxidans can be used for the ex-situ bioremediation of U(VI) contaminated mine water.